Effects of Different Soil Textures on The Yield and Chemical Composition of Alfalfa (Medicago sativa L.) Cultivars Under Mediterranean Climate Conditions - Geren, Hakan; Kir, Behcet; Demiroglu, Gulcan; Tuncer Kavut, Y. (Asian Journal of Chemistry, 2010)
The effects of two soil textures (heavy and light) and five cultivars (Alpha, Barlydia, Verdor, Pioneer-5683, Elci) on the yield and chemical compositions of alfalfa were evaluated under Mediterranean climatic conditions in Izmir, Turkey in 2005 and 2006. The experimental design was a randomized complete blocks design with four replications. Results indicated that, effect of soil texture and cultivar interactions on fresh biomass yields and dry matter and crude cellulose content were found to be significant. Verdor and P-5683 cultivar. had better performances than other cultivars with regard to fresh biomass yield, contents of dry matter, crude protein and crude ash. The alfalfa yields on light soil texture were significantly higher than heavy textured soil.